Preliminary phytochemical and antimicrobial studies on a spike-moss Selaginella inaequalifolia(hook.& grev.) Spring - Irudayaraj, Varaprasadham; M, Janaky; Johnson, Marimuthu; Selvan, Nallayan (Asian Pacific journal of tropical medicine, 2010)
<正>Objective:To screen the anti-cancer spike-mosses for the presence of various bioactivities and to identify the important bioactive chemicals present in Selaginella inaequalifolia(S. inaequalifolia)(Hook.& Grev.) Spring.Methods:Preliminary phytochemical screening was done by following the method of Brindha et al.Antimicrobial study was carried out by disc diffusion method.Results:Results of preliminary phytochemical screening on five different extracts(petroleum ether,benzene,chloroform,ethanol and distilled water) of the spike-moss S.inaequalifolia show the presence steroids,triterpenes,phenolic group,tannin,sugars and catechin.Alkaloids,amino acids,anthraquinone and reducing sugar did not show any positive result.Among the five different extracts,ethanol and chloroform extracts show the presence of maximum number(4 each) of compounds.The results on antimicrobial studies show that all the three microbes[Staphylococcus aureus(S.aureus),Escherichia coli(E.coli) and Candida albicans (C.albicans)]tested are resistant to the ethanol extract and susceptible to petroleum ether extract.The petroleum ether extract shows maximum inhibition with 45 mm of inhibition zone in C.albicans.The inhibition zone in S.aureus and E.coli are 26 mm and 22 mm respectively. Conclusions:The present study shows S.inaequalifolia having potent antibacterial and anticandidal activities.